Rancang Bangun Website Jatim Parkir Center dengan Manajemen Konten Dinamis Menggunakan Laravel Filament - Putra, MZidane Andhika; Roliawati, Dwi; Khalid, Khalid; Yusuf, Ahmad (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study discusses the design and development of the Jatim Parkir Center Website with dynamic content management using the Laravel framework and Filament admin panel. The main objective is to provide an efficient solution for website content management, which was previously handled manually and ineffectively. The development method employed is the Waterfall model, combined with prototyping to ensure usability. The implementation results show that the system provides a simple yet functional interface, including service list management (add, update, delete, and activate/deactivate), Light and Dark display modes, and a secure login page. Based on black box testing, all functions performed optimally, proving that the system supports faster, more accurate, and structured data management. Therefore, this research successfully delivers a flexible CMS solution that is easy to operate and relevant to the company’s digitalization needs.